Does water fluoridation affect the prevalence of enamel fluorosis differently among racial and ethnic groups?. (24th November 2017) - Arora, Shivani; Kumar, Jayanth V.; Moss, Mark Eric
Abstract: Objectives: There are reports showing higher prevalence of enamel fluorosis among African‐American children. This study was conducted to assess whether the effect of water fluoride level on enamel fluorosis is different among different race/ethnicity groups among US school children. Methods: Data from the National Survey of Oral Health of US School Children 1986‐1987 were analyzed to determine the prevalence of enamel fluorosis among 7‐17 year‐old children. The association between race/ethnicity and enamel fluorosis was examined using logistic regression modeling after controlling for potential confounders age, gender, water fluoridation, other sources of fluoride, and region of residence. Results: The prevalence of very mild to severe enamel fluorosis was 20.8 (95% CI, 15.4, 26.3) and 25.7 (95% CI, 15.0, 36.5) percent among non‐Hispanic White and non‐Hispanic Black children, respectively. Neither the adjusted odds ratio of 1.3 (0.8, 2.0) for the non‐Hispanic Black group nor the interaction effect between non‐Hispanic Black and water fluoridation were statistically significant. Conclusions: Enamel fluorosis was not associated with race/ethnicity. Our analysis suggests that exposure to similar levels of fluoride in the water does not appear to place certain race/ethnic groups at a higher risk for developing enamel fluorosis, and lowering the optimal range of drinking water fluoride to a single value of 0.7 ppm will provide a level of protection against enamel fluorosis that will benefit all race/ethnicity groups.